Adherence to high-intensity statin therapy after acute coronary syndrome and its impact on patient outcome. (25th November 2020) - Sulzgruber, P; Sinkovec, H; Kazem, N; Hofer, F; Hammer, A; Koller, L; Todorovic, M; Katsch, F; Gall, W; Duftschmid, G; Heinze, G; Niessner, A
Abstract: Background: Secondary prevention after acute coronary syndrome (ACS) mirrors a key position in the reduction of morbidity and mortality in this highly vulnerable patient population. Especially lipid lowering therapy – via high-intensity statins (atorvastatin and rosuvastatin) – proved to be one of the most beneficial therapeutic approaches for the reduction of re-events and stent thrombosis. However, profound epidemiological measures on adherence to statin intake after ACS remain scare, but seem of major importance in terms of preventing fatal cardiac adverse events. Therefore, we aimed to investigate adherence to high-intensity statin therapy after ACS and its impact on patient outcome from an Austrian nationwide perspective. Methods: Within this population-based national observation all patients presenting with ACS between 04/2011 and 8/2015 in Austria were enrolled. Patient characteristics and co-morbidities were assessed via the Austrian national health insurance system and elucidated according to ICD10 definitions. Adherence to high-intensity statins was investigated according to handing in prescriptions for rosuvastatin and atorvastatin at local pharmacies. Patients were followed prospectively until the primary study endpoint (=mortality) was reached. Cox Regression hazard analysis was used to investigate the impact of non-adherence to high-intensity statin therapy on patient outcome and was adjusted for a comprehensive subset of confounders within the multivariate model. Results: During the observation period a total of 23.240 patients (median age: 65 years [55–75]; male: 67.7% [n=15.728]) met the inclusion criteria. Individuals that died during the index event (n=366; 1.6%), presented with a re-ACS (n=569; 2.4%) or were lost during follow-up (n=158; 0.6%) were not included within the final analysis. Of alarming importance 66.4% (n=15.422) of all patients presenting with ACS did not take high-intensity statins as recommended by current guidelines. The highest rate of drug interruption/end of therapy was observed within the first month after the index event with more than 50% of all cases. During patient follow-up until 01/2018 a total of 3522 (15.2%) individuals died. Non-adherence to high-intensity statins had a strong an independent association with mortality with an adjusted hazard ratio of 1.16 (95% CI: 1.06–1.25; p<0.001) (see Figure 1). Conclusion: The present nationwide investigation highlighted an overall low adherence to high-intensity statins after ACS, with the highest interruption/end of therapy rate within the first month after the index event. Since the intake of high-intensity statins after ACS was associated with a 14% risk reduction for fatal cardiovascular events during the observation period, awareness in terms of drug-adherence and intensified patient follow-up should be promoted, in order to prevent fatal atherothrombotic events. Funding Acknowledgement: Type of funding source: None